Die internationalprivatrechtliche Qualifikation Bestimmung des sachlichen Anwendungsbereichs der Kollisionsnorm: Historische Entwicklung und heutige Dogmatik - Wagner, Leonard Maximilian (Mohr Siebeck, 2025)
Since its discovery, the question of how to identify the relevant choice of law rule has been one of the fundamental problems of private international law. Leonard Wagner outlines the historical development of the discourse on the problem of qualification and, building on this, addresses current issues.
PublicationDate: 20250505
Keywords: Internationales Privatrecht -- Handel -- Franz Kahn -- Qualifikationsgegenstand -- Qualifikationsstatut -- Qualifikationsproblem -- Epistolary Communication (epistolary literature) -- Roman friendship -- Politeness -- Erfolgswert -- Rechtsgeschichte -- Ausländisches Recht, Rechtsvergleichung